FACIES DIFFERENTIATION OF MINERAL AND ORGANIC MATTERS UNDER COASTAL-MARINE SEDIMENTATION CONDITIONS - Tugarova M.A. (My University, 2004)
Coastal-marine sedimentation conditions in the Pechora River delta, Korovinskaya Bay, and intertidal zone of the Pechora Sea are characterized by diverse physicochemical processes that define the differentiation of mineral and organic components of sediments. On the basis of a complex study of abundant observation data, lithostructural and geochemical (including organic-geochemical) features of sediments in different facies circumstances of a common lateral series are considered. Synchronous changes in mineral and organic components are also taken into account. Informative numerical indices characterizing sediments of different facies conditions and lithodynamic–geochemical regimes of their formation are defined. Major factors of sedimentation and early diagenesis are distinguished. Each facies type of sediments is considered a product of sedimentary-diagenetic differentiation of polycomponent substance in certain hydrodynamic and geochemical conditions. These processes are dramatically manifested under deltaic coastal-marine complex conditions that serves as a natural lithodynamic and geochemical barrier.